Quality of Moringa oleifera Leaf and Kiambang (Salvinia molesta) Solid Organic Fertilizer with Banana Peel Bioactivator - Apriani, Desvia Puput; Asngad, Aminah (Universitas Muhammadiyah Surakarta, 2023)
Moringa oleifera leaves and kiambang (Salvinia molesta) can fulfill plants' N, P, and K elements to become solid organic fertilizers with banana peel waste as a bioactivation. This study aimed to determine the quality of solid organic fertilizers for Moringa oleifera leaves and Kiambang with banana peels as a bioactivator based on sensory tests and nutrient content. This study used an experimental method with a factorial pattern. As for factor 1, namely the comparison of ingredients, K1 = 300 g: 200 g and K2 = 200 g: 300 g. Factor 2 is the concentration of bioactivator, M1 = 25 mL and M2 = 30 mL. The results showed that the best quality of Fertilizer from sensory characteristics was demonstrated by the K2M2 treatment in black color, less pungent scent, crumb texture, and a pH of 7. In contrast, the N, P, and K content test was shown by the K1M1 treatment with N content (3.29%), P (0 .10%), and K (0.24%). So that, it can be concluded fertilizers for Moringa oleifera leaves and Kiambang (Salvinia molesta) with banana peel waste as bioactivator have good quality according to SNI 19-7030-2004.